Comparison of the Effectiveness of Elderly Exercise with Static Cycle Exercise on the Depression Level Profile of Elderly Individuals - Kurniawati, Andriana Yuli; Maulina, Luluk (Universitas Muhammadiyah Surakarta, 2024)
Introduction: Depression is a mental disorder that usually manifests as depressed mood, loss of interest or pleasure, feelings of guilt, difficulty sleeping or lack of appetite and concentration. Methods: This type of research is quasi-experimental with a group pretest and posttest design. With a total population of 38 respondents and a total sample of 20 respondents. By using The Geriatric Depression Scale (GDS) as a research instrument. The results of examining the data used the GDS questionnaire which was then processed using the Graphpad prism program. Results: The results showed that there was a significant effect by giving elderly exercise 3 times a week for 5 weeks, and there was an insignificant effect by giving static cycle exercise 3 times a week for 5 weeks. In the elderly exercise group, the GDS score showed a significant decrease, whereas in the static cycle exercise treatment group, the GDS score showed a slight decrease, which means not too significant. Conclusion: The conclusions from this study are that there is a significant effect of giving elderly gymnastics on the depression level profile of elderly individuals, there is an insignificant effect by giving static cycle exercise to the depression level profile of elderly individuals in Mranti Village, Purworejo Regency, and elderly gymnastics is more effective than static cycle exercise. The suggestion that can be given is that physiotherapists are more active in providing exercise programs so that elderly people are always active.